NAD(P)H:quinone oxidoreductase 1 inducer activity of some novel anilinoquinazoline derivatives - Ghorab MM; Alsaid MS; Higgins M; Dinkova-Kostova AT; Shahat AA; Elghazawy NH; Arafa RK (Dove Medical Press, 2016)
Mostafa M Ghorab,1,2 Mansour S Alsaid,1 Maureen Higgins,3 Albena T Dinkova-Kostova,3–5 Abdelaaty A Shahat,1,6 Nehal H Elghazawy,7 Reem K Arafa7,8 1Department of Pharmacognosy, College of Pharmacy, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Department of Drug Radiation Research, National Center for Radiation Research & Technology, Atomic Energy Authority, Cairo, Egypt; 3Jacqui Wood Cancer Centre, Division of Cancer Research, Medical Research Institute, University of Dundee, Dundee, UK; 4Department of Medicine, 5Department of Pharmacology and Molecular Sciences, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 6Phytochemistry Department, National Research Center, Dokki, Giza, 7Zewail City of Science and Technology, 8Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Cairo University, Cairo, Egypt Abstract: The Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response elements pathway enables cells to survive oxidative stress conditions through regulating the expression of cytoprotective enzymes such as NAD(P)H:quinone oxidoreductase 1 (NQO1). This work presents the design and synthesis of novel anilinoquinazoline derivatives (2–16a) and evaluation of their NQO1 inducer activity in murine cells. Molecular docking of the new compounds was performed to assess their ability to inhibit Keap1–Nrf2 protein–protein interaction through occupying the Keap1–Nrf2-binding domain, which leads to Nrf2 accumulation and enhanced gene expression of NQO1. Docking results showed that all compounds can potentially interact with Keap1; however, 1,5-dimethyl-2-phenyl-4-(2-phenylquinazolin-4-ylamino)-1,2-dihydropyrazol-3-one (9), the most potent inducer, showed the largest number of interactions with key amino acids in the binding pocket (Arg483, Tyr525, and Phe478) compared to the native ligand or any other compound in this series. Keywords: Kelch domain, molecular modeling, Keap1/Nrf2, cytoprotection, NQO1 induction